PENGARUH BIAYA PRODUKSI DAN BIAYA OPERASIONAL TERHADAP LABA BERSIH DENGAN VOLUME PENJUALAN SEBAGAI VARIABEL INTERVENING - Yuliani, Fitri; Komarudin, Mochamad Fahru (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2022)
The phenomenon that needs to be studied in manufacturing companies is that the company’s profit falls inversely proportional to the revenue that has risen significantly. The research used quantitative methods, using path analysis with the IBM SPSS Statistics program version 22. The population in this study is the financial statements of PT Ultra Jaya Milk Industry & Trading Company Tbk. The sample in this study is a quarterly financial report in the form of production costs, operational costs, sales volume and net profit of the company in 2011-2019, amounting to 36 samples. The results of this study show that partially production costs and operating costs have a direct positive effect on net profit. Based on the results of the analysis of the production cost line and operating costs, it does not indirectly affect net profit through sales volume as an intervening variable, because the value of the direct influence of production costs and operating costs on net profit is greater than the value of the indirect influence between production costs and operating costs on net profit through sales volume